2011
DOI: 10.1128/aem.05692-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Gordonia and Nocardia Stabilized Foam Formation by Using Bacteriophage GTE7

Abstract: Most activated sludge treatment plants suffer from the presence of foams on the surfaces of their aeration reactors. These are often stabilized by hydrophobic mycolic acid-synthesizing actinobacterial species. A polyvalent Siphoviridae phage, GTE7, which lysed several Gordonia and Nocardia species, is described here. Its genome has a modular structure similar to that described for Rhodococcus phage ReqiDocB7. In laboratoryscale experiments, we showed that GTE7 prevents stabilization of foams by these Gordonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…A similar level of stringent strain specificity has been observed in other actinophages (15)(16)(17)(18)(19)(20)(21)27). Possible explanations include an absence of a compatible receptor site in the resistant host cell, absence of appropriate molecular machinery to support infection, or possession of phage resistance systems like clustered regularly interspersed repeat (CRISPR) systems, restriction modification (RM) systems, and abortive infection (Abi) systems (28).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A similar level of stringent strain specificity has been observed in other actinophages (15)(16)(17)(18)(19)(20)(21)27). Possible explanations include an absence of a compatible receptor site in the resistant host cell, absence of appropriate molecular machinery to support infection, or possession of phage resistance systems like clustered regularly interspersed repeat (CRISPR) systems, restriction modification (RM) systems, and abortive infection (Abi) systems (28).…”
Section: Resultsmentioning
confidence: 89%
“…Pellets were resuspended in 8 M urea to a final volume of 100 l prior to analyses at the Mass Spectroscopy and Proteomics Facility at the La Trobe Institute of Molecular Sciences (Melbourne, Australia). Peptides reconstituted in 0.1% formic acid and 2% acetonitrile (buffer A) were loaded onto a trap column (C 18 PepMap, 300-m inner diameter [i.d. ], 2-cm trapping column [Thermo-Fisher Scientific, Scoresby, Australia]) at 5 l/min for 6 min and washed for 6 min before switching the precolumn in line with the analytical column (Vydac MS C 18 , 75-m i.d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Bacteriophages were grown in lab and a sufficient amount of bacteriophages were applied to their respective hosts. The data showed CFU/ml decreased markedly in the presence of NOC1, NOC2, and NOC3 when collectively applied to the lab scale reactor.…”
Section: Applicability Of Phage To Lab Scale Reactormentioning
confidence: 99%
“…1,2 In the previous study, we had isolated and tested specific bacteriophages against Nocardioforms -NOC1, NOC2 and NOC3 and showed that they can be used effectively to curb foaming. Their host range was determined and genome sequences studied.…”
Section: Introductionmentioning
confidence: 99%